Augmented Reality (AR) and Virtual Reality (VR) in Marketing - Rathore, Neetu (Management Journal for Advanced Research, 2024)
Technology has brought up a revolution in the ways we think, act and perceive things. In our day to day lives, technology plays a very important role. All the traditional ways of working are taker over by modern ways due to new technological innovations every day. One such innovation is the use of Augmented reality, virtual reality and mixed reality in almost all fields of operation whether it is spots, entertainment, health, education or marketing. These technologies have given consumers the level of satisfaction that they never experienced before. They take the consumers in almost altogether a new realm of imagination. Shopping for the consumers becomes fun filled with emotions and personalisation. Whether it is marketing through AR, VR or MR companies are able to earn more profits as well as satisfy their customers. The evolutions of these technologies is not new but their usage in marketing field is somewhat in early stage, but it is growing each day with a mix of creativity in the way businesses interact and attract customers. There are few considerations while using these techniques in marketing to make the impact strong and long lasting in the minds of consumer, if followed, it may reap more profits for the companies. The future of these technologies contains many more surprises for consumers and seems very bright.